AN AUDIT OF TRANSIENT LOSS OF CONSCIOUSNESS. Issue 10 (9th September 2014) - Wynford-Thomas, Ray; Johnston, Ann; Jones, Elizabeth; Corkill, Robin
Abstract : Aim: The diagnosis of transient loss of consciousness (TLOC) can be challenging and its misdiagnosis may lead to inappropriate referrals and be potentially dangerous for patients. Methods: In light of this, we audited 58 case notes of patients presenting to A&E with a suspected seizure, TLOC or collapse. A proforma was prepared from NICE guidelines and European Society of Cardiology guidelines, and data collected. Results: We found deficiencies in the recording of posture (47, 81%), vagal symptoms (30, 52%), limb movements (26, 45%) and post-ictal state (32, 55%). DVLA instructions were given to 3 patients (5%). 8 (14%) did not have an ECG. Investigations requested included a CT head (23, 40%), telemetry (9, 16%) and EEG (3, 5%). 7 (12%) were referred to cardiology and 6 (10%) to neurology. 28 (48%) had no speciality referral. Unfortunately, 8 (14%) died following admission; all had an ECG, but only 1 had a speciality referral. Conclusion: Overall we found poor documentation in key areas of the clinical history and DVLA information provision. There is significant scope for improving diagnostic accuracy and to aid timely and appropriate investigation and referral. We therefore plan to implement a proforma to aid clinical diagnostic decision-making in the A&E and aim to re-audit.